Naturalistic Driving Behaviour and Self-Regulation Practices Among Older Drivers with Bilateral Cataract: a Prospective Cohort Study - Agramunt, Seraina (Curtin University, 2018)
This naturalistic study examined older drivers before first eye, after first eye, and after second eye cataract surgery by examining how objective visual measures and other factors influenced driving habits, exposure, adverse events and driver self-regulation. The results provide evidence for timely cataract surgery, the inclusion of contrast sensitivity when assessing fitness to drive for older drivers and driver self-regulation as a strategy to improve road safety as older drivers wait for cataract surgery.